Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/toxins11120716
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Malawian Farmers on Pre- and Post-Harvest Crop Management to Mitigate Aflatoxin Contamination in Groundnut, Maize and Sorghum—Implication for Behavioral Change

Abstract: A knowledge, attitude and practice (KAP) study was conducted in three districts of Malawi to test whether the training had resulted in increased knowledge and adoption of recommended pre- and post-harvest crop management practices, and their contribution to reducing aflatoxin contamination in groundnut, maize and sorghum. The study was conducted with 900 farmers at the baseline and 624 farmers at the end-line, while 726 and 696 harvested crop samples were collected for aflatoxin testing at the baseline and end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 22 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…This practice was notable in Emsoo ward, and one of the caregivers said "Last year, all of my neighbour's produce got spoilt but she refused to dispose off; they consumed all of it." Lack of knowledge on the health effects associated with mycotoxins (Mboya & Kolanisi, 2014 ) and food shortage are among the contributing factors for the use of spoilt grains for human consumption and as animals feed (Anitha et al., 2019 ; Matumba et al., 2016 ). The study participants showed a general lack of awareness on the health effects associated with mycotoxins on humans.…”
Section: Discussionmentioning
confidence: 99%
“…This practice was notable in Emsoo ward, and one of the caregivers said "Last year, all of my neighbour's produce got spoilt but she refused to dispose off; they consumed all of it." Lack of knowledge on the health effects associated with mycotoxins (Mboya & Kolanisi, 2014 ) and food shortage are among the contributing factors for the use of spoilt grains for human consumption and as animals feed (Anitha et al., 2019 ; Matumba et al., 2016 ). The study participants showed a general lack of awareness on the health effects associated with mycotoxins on humans.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study by Anitha et al. (2019) observed that despite adverse weather conditions mean aflatoxin levels in grains were reduced from 83.6 to 55.8 ppb as a result of training farmers on aflatoxin‐related issues.…”
Section: Current Aflatoxin‐contamination Prevention Methodsmentioning
confidence: 99%
“…As for inferential analysis, the Wilcoxon signed rank test (Seetha et al, 2019), a nonparametric alternative to the paired t test, is employed to examine the change in livelihood indicators over time. Furthermore, harnessing the recall data, the panel regression method (Tsusaka and Otsuka, 2013) is adopted to identify the change in livelihood indicators while determining and controlling for factors affecting their levels.…”
Section: Discussionmentioning
confidence: 99%